2017
DOI: 10.1007/s11356-017-0221-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal water chemistry variability in the Pangani River basin, Tanzania

Abstract: The stable isotopes of δO, δH, and Sr/Sr and dissolved major ions were used to assess spatial and seasonal water chemistry variability, chemical weathering, and hydrological cycle in the Pangani River Basin (PRB), Tanzania. Water in PRB was NaHCO type dominated by carbonate weathering with moderate total dissolved solids. Major ions varied greatly, increasing from upstream to downstream. In some stations, content of fluoride and sodium was higher than the recommended drinking water standards. Natural and anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Water quality within Arusha City has been previously studied; the concentration of fluorides in rivers [ 18 ], nitrate transformations [ 19 ], and physical and chemical characteristics of the groundwater systems [ 20 ]. Furthermore, the level of progesterone hormones in rivers and stabilization ponds [ 21 ], and the quantity of macro- and microplastics within the city [ 22 ] were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Water quality within Arusha City has been previously studied; the concentration of fluorides in rivers [ 18 ], nitrate transformations [ 19 ], and physical and chemical characteristics of the groundwater systems [ 20 ]. Furthermore, the level of progesterone hormones in rivers and stabilization ponds [ 21 ], and the quantity of macro- and microplastics within the city [ 22 ] were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that the reservoir has high trap efficiency ranging from 20% to 90% [13]. Additionally, the estimate showed that Nyumba Ya Mungu reservoir has high residence time of about 18 months [14]. High trap efficiency and high residence time causes the reservoir to be a sink of nutrients, organic carbon and metals [13,14].…”
Section: Introductionmentioning
confidence: 99%